2018
DOI: 10.1253/circj.cj-17-1381
|View full text |Cite
|
Sign up to set email alerts
|

Alamandine Protects the Heart Against Reperfusion Injury via the MrgD Receptor

Abstract: These results suggest that the cardioprotective effects of alamandine against I/R injury are, in part, related to the activation of antioxidant and antiapoptotic enzymes via the MrgD receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…These results indicated that alamandine improved LPS-induced cardiac dysfunction and increased cardiac contractility. 23) Additionally, alamandine has cardioprotective effects on ischemia-reperfusion Injury by activating the antioxidant and antiapoptotic enzymes via the MrgD receptor. Alamandine improved reperfusion-induced changes in LVEDP, LVDP, ±dP/dt, and coronary blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that alamandine improved LPS-induced cardiac dysfunction and increased cardiac contractility. 23) Additionally, alamandine has cardioprotective effects on ischemia-reperfusion Injury by activating the antioxidant and antiapoptotic enzymes via the MrgD receptor. Alamandine improved reperfusion-induced changes in LVEDP, LVDP, ±dP/dt, and coronary blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that MrgD KO mice presented a reduction in atrial natriuretic peptide mRNA with no changes in brain natriuretic peptide mRNA. Accordingly, Park et al (23) have recently shown that alamandine can stimulate atrial natriuretic peptide secretion in isolated atria, and this effect was completely blocked by a MrgD receptor antagonist. The reduction of atrial natriuretic peptide expression in MrgD KO mice could be implicated in the pathogenesis of DCM observed in these animals.…”
Section: H129mentioning
confidence: 99%
“…The anti-hypertrophic 135 , anti-hypertensive 73 , anti-inflammatory 120 and cardioprotective 6 properties of angiotensin 1-9 have been described. alamandine was discovered in 2013 as an anti-hypertensive agent 67 , and the cardioprotective properties of this compound have since been described 155,156 . NaTure revIewS | CARdiology of ACE2 might have a therapeutic effect, a recombinant human ACE2 (rhACE2) has been developed and tested in animal models.…”
Section: Box 1 | Timeline Of the Discoveries Related To The Counter-rmentioning
confidence: 99%